Fluorophobic Effect Driven Self‐Organization of Semifluorinated Alkyl Chain Substituted Conjugated Polymer. Issue 14 (2nd May 2017) - Heo, Youn‐Jung; Kim, Jihong; Jeong, Hyung‐Gu; Jang, Soo‐Young; Hwang, Hansu; Kim, Yeong‐A; Lim, Dae‐Hee; Kim, Dong‐Yu
Abstract : Semifluorinated alkyl chain substituted conjugated polymer, SFA‐P3DT, is synthesized to induce the formation of nanofibrillar structure via intense fluorophobic effect. The resultant well‐ordered nanostructure of SFA‐P3DT improves the charge carrier mobility of organic thin film transistors. This study highlights the remarkable properties of semifluorinated alkyl chain for further introduction into other conjugated polymers. Abstract : This paper reports on the effect of a semifluorinated alkyl side chain for achieving a self‐organized nanostructure to facilitate the efficient charge carrier transport. So far, semifluorinated alkyl side chains have rarely been introduced into semiconducting polymers, despite their interesting properties such as hydrophobicity, thermal stability, and solvent resistance, as well as self‐organization. Herein, this study synthesizes the semifluorinated alkyl chain introduced poly(3‐dodecylthiophene), SFA‐P3DT, and demonstrates that self‐organization of SFA‐P3DT is intensely induced in nonfluorous solvent by the so‐called fluorophobic effect, resulting in the formation of nanofibrillar structure. In presence of the semifluorinated alkyl side chain, organic thin film transistor (OTFT) devices exhibit the improved charge carrier mobility than that of poly(3‐dodecylthiophene) with hydrocarbon alkyl chain. Moreover, higher charge carrier mobility can be obtained from the nonfluorous solvent, in comparison to the fluorous solvent, confirming the crucial role of fluorophobic effect. These observations suggest that the introduction of semifluorinated alkyl chains into a conjugated polymer may enhance the performance of OTFTs through the development of a well‐ordered nanostructure via self‐organization by fluorophobic effect, which, in turn, facilitates the efficient charge carrier transport.